Adsorption of Toxic Metal Ions onto Silica with Covalently Bound 8-Hydroxyquinoline - E.S. Yanovska; O.V. Glushchenko; V.I. Karmanov; O.Yu. Kichkiruk; V.A. Tertykh (Adsorption Science & Technology)
8-Hydroxyquinoline covalently bound to silica via a one-stage Mannich reaction was used as an adsorbent for the pre-concentration of Pb(II), Cd(II), Zn(II) and Mo(VI) ions from aqueous solutions in the dynamic mode following determination of their concentrations by X-ray fluorescence methods. The adsorption of Pb(II), Cd(II), Zn(II) and Mo(VI) ions was studied from individual and complex multi-component solutions of both natural and technogenic origins. Peculiarities associated with the simultaneous X-ray fluorescence determination of mixtures of toxic metal ions in a solid matrix are discussed.